2017
DOI: 10.3390/genes8040113
|View full text |Cite
|
Sign up to set email alerts
|

The MYCN Protein in Health and Disease

Abstract: MYCN is a member of the MYC family of proto-oncogenes. It encodes a transcription factor, MYCN, involved in the control of fundamental processes during embryonal development. The MYCN protein is situated downstream of several signaling pathways promoting cell growth, proliferation and metabolism of progenitor cells in different developing organs and tissues. Conversely, deregulated MYCN signaling supports the development of several different tumors, mainly with a childhood onset, including neuroblastoma, medul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 220 publications
(347 reference statements)
2
122
2
Order By: Relevance
“…Although the etiology of neuroblastoma is not completely understood, a number of genetic alterations are present in both familial and sporadic neuroblastoma. Among the genes most frequently altered in neuroblastoma is MYCN, which is amplified in about 25% of all neuroblastoma cases and whose expression positively correlates with advanced disease stage (1). High levels of MYCN protein in neuroblastoma patients correlate with metastasis and other hallmarks of poor prognosis (2).…”
mentioning
confidence: 99%
“…Although the etiology of neuroblastoma is not completely understood, a number of genetic alterations are present in both familial and sporadic neuroblastoma. Among the genes most frequently altered in neuroblastoma is MYCN, which is amplified in about 25% of all neuroblastoma cases and whose expression positively correlates with advanced disease stage (1). High levels of MYCN protein in neuroblastoma patients correlate with metastasis and other hallmarks of poor prognosis (2).…”
mentioning
confidence: 99%
“…In neuroblastoma, a genetic aberration of MYCN ampli cation is related to a poor prognosis and failure of therapy. MYCN targeted therapy has been proposed as a new strategy for cancer treatment, and many effort has been made to develop direct and indirect MYCN inhibitors with potential clinical applications [45].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, a small fraction of unilateral cases lack identified RB1 mutations, so it was long postulated that an alternative mechanism of retinoblastoma genesis might be possible. As part of an international team, in 2013 we identified that 1.4% of unilateral retinoblastoma, lacking RB1 mutations, instead showed amplification of MYCN (Rushlow et al, ) (Figure ), a transcription factor–encoding gene more frequently associated with the pediatric peripheral nervous system tumor, neuroblastoma (Ruiz‐Perez, Henley, & Arsenian‐Henriksson, ). This finding raises interesting questions about the parallels between retinoblastoma and other neuronal tumors (see below).…”
Section: Retinoblastoma Overviewmentioning
confidence: 99%